2014
DOI: 10.1128/iai.02225-14
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Streptococcus pneumoniae Transcriptome during Transition from Biofilm Formation to Invasive Disease upon Influenza A Virus Infection

Abstract: f Streptococcus pneumoniae is a leading cause of infectious disease globally. Nasopharyngeal colonization occurs in biofilms and precedes infection. Prior studies have indicated that biofilm-derived pneumococci are avirulent. However, influenza A virus (IAV) infection releases virulent pneumococci from biofilms in vitro and in vivo. Triggers of dispersal include IAV-induced changes in the nasopharynx, such as increased temperature (fever) and extracellular ATP (tissue damage). We used whole-transcriptome shotg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 81 publications
5
129
0
Order By: Relevance
“…Through the combination of an in vitro biofilm model ( Fig. 2A) and transcriptional analysis of the bacterial populations comprising this model (23,36), antigens were identified that were significantly up-regulated in biofilm-released pneumococci demonstrating increased virulence. In addition to providing target antigens, the biofilm model served another key purpose in this study: Namely, S. pneumoniae is a human pathogen that, with the exception of a few strains, cannot cause invasive disease in mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the combination of an in vitro biofilm model ( Fig. 2A) and transcriptional analysis of the bacterial populations comprising this model (23,36), antigens were identified that were significantly up-regulated in biofilm-released pneumococci demonstrating increased virulence. In addition to providing target antigens, the biofilm model served another key purpose in this study: Namely, S. pneumoniae is a human pathogen that, with the exception of a few strains, cannot cause invasive disease in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, antigen targets up-regulated in biofilm-released bacteria were prepared as recombinant proteins and tested for protection relative to the well-established S. pneumoniae surface protein antigen (PspA), which is one of the best-studied protein protective vaccine candidates and also is up-regulated during virulence transition ( Fig. 2E) (36)(37)(38). Under these conditions, all antigens except DexB showed protection comparable to PspA, with two antigens, GlpO (an α-glycerophosphate oxidase) and PncO (a bacteriocin ABC transporter transmembrane protein), demonstrating promising individual protection surpassing that of PspA.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza neuraminidase cleaves sialic acid from sialylated airway mucins enabling pneumococcal strains that are able to metabolize these sugars to increase their rates of division (Siegel et al, 2014). Moreover, elevated temperature and extracellular ATP occurring during viral infection can trigger the release of pneumococci from biofilms and induce changes in the bacterial transcriptome, associated with improved bacterial stress responses, altered metabolism and increased virulence (Marks et al, 2013;Pettigrew et al, 2014). Viral infections differentially impact the formation and maintenance of P. aeruginosa biofilms: while the release of extracellular iron and transferrin stimulates biofilm formation after RSV infection, the release of hydrogen peroxide during HRV infection triggers the release of P. aeruginosa and facilitates transmigration of bacteria through the epithelial layer and might thus contribute to the dissemination of infection (Chattoraj et al, 2011b;Hendricks et al, 2016).…”
Section: Other Mechanismsmentioning
confidence: 99%
“…pneumoniae and S. pneumoniae after direct binding to RSV, both of which were associated with increased pneumococcal virulence in mice (128,134). …”
Section: Viral Modulation Of Bacterial Virulencementioning
confidence: 99%
“…Temperature increases modelling fever have been found to trigger the expression of immune evasion factors in the opportunistic pathogen Neisseria meningitidis (132). Fever and other host cell damage signals induced by IAV infection have been shown to stimulate S. pneumoniae biofilm dispersal, leading to bacteria with an increased ability to disseminate from the nasopharynx of mice, resulting in infection of sites such as the lung and the blood (133,134). Corroborating these studies, Leung et al (135) found the microbiome of IAV positive patients contained significantly higher expression levels of genes involved in cell motility and signal transduction, such as chemotaxis and flagellum assembly, compared to those of IAV negative pneumonia patients.…”
Section: Viral Modulation Of Bacterial Virulencementioning
confidence: 99%